AN ANALYSIS ON TYPES OF PHRASES USED IN TAYLOR SWIFT SONG’S LYRIC FROM “THE TORTURED POETS DEPARTMENT” ALBUM - Maulidyah, Zesifah; Syamsuar, Fauzi; Lestari, Noviana (Jurnal Review Pendidikan dan Pengajaran, 2024)
a phrase is a group of words which have a grammatical relationship to each other, and which together form a structural unit. The study aims to find out types of phrases used in song’s lyric in The Tortured Poets Department album by Taylor Swift, the data analyzed is Taylor Swift’s selected songs in The Tortured Poets Department album, namely The Tortured Poets Department, Guilty as Sin, and Fortnight. The research design used is descriptive with a qualitative approach to analyze the data using the theory of Moleong (2017, p.6) related to type of phrases. The result of the study showed that there are some types of phrases used in the selected songs in The Tortured Poets Department album by Taylor Swift, i,e. noun phrases, verb phrases, adjective phrase, prepositional phrase, and adverb phrase. From the analysis that have been done, 49 occurrences of phrases were found in the three songs. Noun phrases consists of 19 occurrences, verb phrases consist of 15 occurrences, adjective phrases consist of 2 occurrences, prepositional phrases consist of 6 occurrences, and adverb phrases consists of 24 occurrences. Therefore, the result shows that the most phrase found in selected song in The Tortured Poets Department album by Taylor Swift is adverb phrases. This research can be useful for further researcher who are interested in conducting research on types of phrases analysis.